THE INFLUENCE OF PRINCIPALS' LEADERSHIP AND WORKLOAD ON TEACHER PERFORMANCE THROUGH SELF-EFFICACY IN MADRASAH TSANAWIYAH - Wati, Sulistia; Yahya, Fata Asyrofi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to explore the impact of leadership style and workload on teacher performance through self-efficacy, with an emphasis on efforts to increase self-efficacy as the main motivation. The survey method was used to collect data based on probability sampling from 30 teachers at MTs Darul Falah Sukorejo. Data collection was carried out using a questionnaire consisting of a Likert scale with 4 alternative answers. PLS-SEM analysis is used to analyze data and test construction infrastructure and variables measuring problem-solving abilities. The results of the analysis show that the Principal's Leadership on Self-Efficacy (ẞ-0.151; p-0.135) has an insignificant effect. In addition, self-efficacy was proven not to mediate the effect of principal leadership (ẞ-0.034: p-0.221) and workload (ẞ-0.121; p-0.057) on teacher performance. The emphasis of this research is the importance of integrating training that focuses on increasing teacher self-efficacy. The recommendations of this research include providing support for professional development programs, as well as encouraging school principals to adopt a supportive leadership style and provide ongoing support. Thus, this research can become a basis for increasing self-efficacy through a deeper understanding of the influence of leadership style and workload on their performance, making a significant contribution to efforts to improve the quality of education.